Co-opted boards and bidder performance - Syed Shams; Hoa Luong; Nafisa Zabeen Ovi (China Accounting and Finance Review)
Defining co-opted directors as those who join a company’s board after an incumbent chief executive officer assumes office, this study aims to investigate the influence of co-opted boards on bidder performance. This study applies ordinary least squares regression analyses to a sample of 8,939 acquisition observations announced by US firms spanning the 1999–2019 period. Event study methodology was employed to capture the market response to acquisition announcements. Propensity score matching technique, a two-stage least squares instrumental variable approach and model selection through the Lasso method were performed for robustness and endogeneity correction purposes. The results depict a significant negative relationship between a co-opted board and return to acquirers, suggesting that managers under co-opted boards make value-destructing Mergers and Acquisitions deals. We also show that the relationship between board co-option and acquisition performance is positively moderated by institutional ownership while being negatively moderated by an entrenched board. Our additional tests reveal that board co-option reduces acquisition efficiency and leads to worse financial performance. This study offers important implications for regulators and policymakers by highlighting how poor monitoring of the board of directors can influence announcement returns. To the best of the authors’ knowledge, this paper appears to be the first investigation that makes a link between board co-option and various dimensions of acquisition decision.